(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In combustiology, the treatment of victims with extensive deep skin burns is the most difficult task. The share of surgeries with unsatisfactory results of autograft engraftment still remains significant, which makes the problem of surgical skin restoration especially urgent in patients with extensive deep burns and a shortage of skin donor resources.